An innovative I-beam to hybrid fabricated column connection: Experimental investigation. (1st October 2017) - Sadeghi, Seyed Nima; Heidarpour, Amin; Zhao, Xiao-Ling; Al-Mahaidi, Riadh
Highlights: An innovative modular connection for steel structures is proposed. Connection behaviour is investigated experimentally and numerically. Connection has higher moment capacity than that of conventional connections. Modularity of the connection improves construction time and quality. Connection is re-usable after building is damaged or in temporary structures. Abstract: Hybrid fabricated columns (HFCs) have been investigated by researchers during the past two decades. Many researchers have reported higher load-bearing capacity, post-buckling strength and better energy absorption as the main advantages of this type of column compared to other structural sections. This provides an opportunity for the construction industry and designers to utilise these superior properties in building more reliable structures. However, no matter how capable and reliable a column is, it still needs a robust connection to make the use of this column in construction viable. Since the topic of connections between these columns and I-beams has been untouched, the authors decided to study this knowledge gap. In this research, a new generation of modular connections is proposed by the authors, referred to hereafter as M-HFC. The performance of this connection has been tested experimentally. In addition, a three-dimensional finite element model has been developed to simulate the behaviour of the connection. The results show that this connection is a fully resistant and semi-rigid connection according to the standard classifications, which makes it a good choice for use in moment frames.